2017
DOI: 10.22373/biotik.v4i1.1068
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Mikroskopis Hati Ikan Seurukan (Osteochilus vittatus) dari Sungai Krueng Sabee Kabupaten Aceh Jaya yang Tercemar Limbah Penggilingan Bijih Emas

Abstract: This research is to observe the Seurukan (Osteochilus vittatus) fish liver microscopic structure in Krueng Sabee river, Aceh Jaya Regency. Fish and river water samples were taken from May to June 2015. Histological techniques and research parameters was conducted in FMIPA Microtechnic Laboratory, Syiah Kuala University, while river water and Seurukan fish mercury level was analyzed in Balai Riset dan Standarisasi Industri, Banda Aceh. Completely Randomized Design was applied of the research with three treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…The liver and kidney in the control treatment were observed normal (Figure 1), meanwhile, liver and kidney in other treatments were showed some lesions and damage. Maharajan et al (2016) and Sari et al (2016) stated that the liver became the object that most often examined because the liver is the target organ to obtain an environmental impact and a correlation between environmental factors and structure and function of hepatic cells. Biotoxin, parasite, bacteria, some pollutants such as pesticides and hydrocarbon are sometimes found in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The liver and kidney in the control treatment were observed normal (Figure 1), meanwhile, liver and kidney in other treatments were showed some lesions and damage. Maharajan et al (2016) and Sari et al (2016) stated that the liver became the object that most often examined because the liver is the target organ to obtain an environmental impact and a correlation between environmental factors and structure and function of hepatic cells. Biotoxin, parasite, bacteria, some pollutants such as pesticides and hydrocarbon are sometimes found in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In Aceh itself, the heavy metal analysis in water, sediments, and fish from aquatic environment have been reported (Ukhty et al, 2020;Rizkiana et al, 2017;Supriatno & Lelifajri, 2009). Nonetheless, another study conducted in Riau Islands Province, Indonesia, reported significant contamination of Pb in Nerita lineata, with the minor presence of other heavy metals (Cu and Zn) (Sari et al, 2016). The same study also suggested that the accumulation was significantly higher in the shell than in the flesh of N. lineata (Sari et al, 2016).…”
Section: Distribution Pattern Of Pb and Zn Contamination In Rivers Ne...mentioning
confidence: 90%
“…Nonetheless, another study conducted in Riau Islands Province, Indonesia, reported significant contamination of Pb in Nerita lineata, with the minor presence of other heavy metals (Cu and Zn) (Sari et al, 2016). The same study also suggested that the accumulation was significantly higher in the shell than in the flesh of N. lineata (Sari et al, 2016). The inconclusive results from the stated studies could be associated with different sampling locations; meaning different environment characteristics as well as surrounding anthropogenic activities.…”
Section: Distribution Pattern Of Pb and Zn Contamination In Rivers Ne...mentioning
confidence: 94%
“…Selain insang, ginjal juga termasuk organ yang berpengaruh dalam osmoregulasi karena berperan dalam proses filtrasi. Sebagai organ detoksifikasi, akumulasi logam berat dapat terdeteksi pada organ hepar karena menjadi organ target bagi toksikan (Sari et al, 2016).…”
Section: Pendahuluanunclassified